ANALISIS IMPLEMENTASI KEBIJAKAN PENGENDALIAN PERTUMBUHAN PENDUDUK DI PROVINSI BENGKULU (Studi Pada Kantor Perwakilan Badan Kependudukan dan Keluarga Berencana Nasional Provinsi Bengkulu) - Alfrida Toding Rante; Evi Lorita; Harius Eko Saputra (Professional: Jurnal Komunikasi dan Administrasi Publik, 2018)
This research aims to describe how the implementation of population growth control policy in Bengkulu Province. This research based on the rate of population growth which always experienced a high increase caused by the increase of Total Fertillity Rare (TFR). This research is used George Edrward III approoach implentation model of communication, resources, disposition and bureaucratic structure. The method used in this research is descriptive qualitative. Data collection techniques used were interviews, obeservations and documentation. The results of this research is that the implementation of population control policy in Bengkulu Province has been effective enough, altough still found few of obstacles and problems in the implementation. By using the approach of George Edward III, it can be analyzed that the implementation KKBPK Program in Bengkulu Province has been running as has been determined, although there are still some indicators which are insufficient. The recomendations of this reseasrch are (to BKKBN office of Bengkulu Province): 1. should to improve communication between implementer, stakeholders, and cross-sector partners; 2. Should increase human and non-human resources (means, facilities and infrastructure); 3. Should to improve the nature of honesty and commitment in carrying out its duties and functions; 4. Should to maintain coordination among institutions or organizations.